Successful Surgical Treatment of “Complex” Abdominal Echinococcosis - A. B. Goncharov; Yu. A. Stepanova; V. S. Shirokov; I. A. Turchenko; Yu. A. Kovalenko; D. V. Kalinin; B. N. Gurmikov; A. V. Zhao (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to present the difficulties of surgical treatment of patients with multiple and combined echinococcal lesions. Key points. A 47-year-old patient who lived in Central Asia for up to 29 years of age was diagnosed with multiple echinococcosis of the abdominal cavity (CE1-2): II, Ivb, V, VI, VII segments of the liver, upper and lower poles of the spleen, lesser and greater omentum, small intestine, subphrenic space, area of the hepatoduodenal ligament, gastrocolic ligament. Surgical intervention was performed: atypical resection of liver segments V, VI, VII, subtotal pericystectomy, cholecystectomy, subtotal pericystectomy of cysts of II and IVb liver segments, subtotal pericystectomy of splenic cysts, resection of the greater omentum, echinococcectomy of the lesser omentum, mesentery of the small intestine, hepatoduodenal ligament, gastrocolic ligament, drainage of the abdominal cavity. Pericystectomy was carried out according to the technique of the National Medical Research Center of Surgery named after A. Vishnevsky.Conclusion. Due to the peculiarities of the course of helminthiasis and the pronounced variability of the lesion, it is extremely difficult to develop universal and effective treatment algorithms. The presented clinical observation demonstrates an example of the successful use of special surgical tactics for the treatment of “complex” echinococcosis of the abdominal cavity with good long-term follow-up results.